Impact of Bacillus subtilis supplemented feed on growth and biochemical constituents in Labeo rohita fingerlings - Asma Chaudhary (Elsevier, 2021)
The study investigated the potential of probiotic isolate Bacillus subtilis AsCh-A4 (Accession No. MF543124) fermented feed to improve growth profile of Labeo rohita fingerlings. Morphometric measurements and nutritional indices of control and experimental groups were compared fortnightly in 90 days experiment. The formulated fish feed was fermented by Bacillus subtilis AsCh-A4 up to seven days and administered at 3% (b/w) with live (G1) and dead (G2) bacterium. G1 group showed significant higher values of DG (Daily gain) and RGR% (percent relative growth rate) in wet body weight than control and G2 while Specific Growth Rate (0.08 – 0.11%) in G1 within phase IV – VI followed by G2 (0.07%) at phase IV over control group. In all groups, the computed condition factor was 1.13, 0.91, 1.09 indicating isometric fish growth. Significantly increased body contents i.e., total protein (phase IV – VI), total carbohydrate (phase V) in G1 and DNA (phase IV) in G1 as well as G2 (phase II – III). Moreover, no significant change was assessed in total lipids, cholesterol, RNA contents, Alkaline phosphatase, Alanine aminotransferase, protease and somatic indices in all groups. Aspartate aminotransferase and acid phosphatase were significantly decreased in G1 (phase II – III) and G2 (phase III) while amylase increased in G1 (phase II). These results clearly demonstrated the growth promoting effect of the probiotics for rohu fish.